2022
DOI: 10.3389/fitd.2022.875031
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Surveillance in Field-Collected Mosquitoes From Pernambuco-Brazil, During the Triple Dengue, Zika and Chikungunya Outbreak of 2015-2017

Abstract: The (re) emergence of arboviruses around the world is a public health concern once severe outbreaks are usually associated with these infections. The co-circulation of Dengue (DENV), Zika (ZIKV) and Chikungunya (CHIKV) viruses in the past few years has caused a unique epidemic situation in Brazil. The northeast region of the country was the most affected by clinical complications from such arboviruses’ infections, including neurological disorders caused by ZIKV. In this particular region, Aedes mosquitoes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Data obtained here showed that 17 pools of C. quinquefasciatus were positive for ZIKV, and six of these exhibited no evidence of blood meal, indicating that the virus was replicating in the mosquito, rather than being recently acquired by hematophagy. Similar data was reported by Krokovsky et al (2022) [17], who screened 549 pools (~2500 C. quinquefasciatus) collected in Recife and its Metropolitan Area, and found ZIKV in 49 polls of non-engorged females. A vector surveillance conducted in Vitória, Espirito Santo State (Southeastern Brazil), also showed the presence of ZIKV in field-caught C. quinquefasciatus mosquitoes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Data obtained here showed that 17 pools of C. quinquefasciatus were positive for ZIKV, and six of these exhibited no evidence of blood meal, indicating that the virus was replicating in the mosquito, rather than being recently acquired by hematophagy. Similar data was reported by Krokovsky et al (2022) [17], who screened 549 pools (~2500 C. quinquefasciatus) collected in Recife and its Metropolitan Area, and found ZIKV in 49 polls of non-engorged females. A vector surveillance conducted in Vitória, Espirito Santo State (Southeastern Brazil), also showed the presence of ZIKV in field-caught C. quinquefasciatus mosquitoes.…”
Section: Discussionsupporting
confidence: 87%
“…From 2015-2017, extensive mosquito surveillance was conducted in the metropolitan area of Recife (MAR), during the triple epidemics of DENV, CHIKV, and ZIKV, to evaluate virus circulation in the urban mosquitoes A. aegypti and C. quinquefasciatus [17]. This surveillance, combined with vector competence studies, supported the role of C. quinquefasciatus in ZIKV transmission in Recife [18].…”
Section: Introductionmentioning
confidence: 99%
“…No tested pool showed positivity outside of the rainy season. Our findings highlight the importance of establishing a defined surveillance timeframe or targeted sampling approach in hotspots, in which active human dengue cases are identified, which others have shown increases mosquito positivity rates (Krokovsky et al, 2022). As such, implementing arbovirus testing in mosquitoes should be done using a more targeted approach that could be more cost-effective.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the presence of virus in a population does not necessarily relate to transmission. Mosquitoes will often be incidental carriers of pathogens circulating in the environment and may not be responsible for transmission [10][11][12] . There is no "smoking gun" in terms of transmission proofs from eld-collections of vertebrates or mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Haematophagous insects can yield information on local pathogen prevalence without being part of the transmission cycle. For example, collections of tsetse ies in Tanzania 10 and Culex mosquitoes in the Brazilian Amazon 11 yielded malaria parasites while urban Culex collections identi ed dengue, Zika and chikungunya viruses in Pernambuco, Brazil 12 .The presence of non-vector-borne pathogens, such as hepatitis C virus 8 and H5N1 virus 13 have also been noted in mosquito collections. Xeno-surveillance might also be used to detect vertebrate antibodies to pathogens.…”
Section: Introductionmentioning
confidence: 99%